Studies on the High-yielding Techniques for Lei Bamboo (Phyllostachys praecox C.D. Chu et C.S. Chao) Shoot-producing Forest - Wei, Fang; Xueke, Lu; Qunchao, Huang; Bihen, Huang; Junchao, He (Indian Forester, 1999)
In order to increase the shoot yield and to move up the shooting season of Lei Bamboo (Phyllostachys praecox C.D. Chu et C.S. Chao) forest, an experiment was carried out in Zhejian Province, China, to test the effectiveness of covering the forest land and application of fertilizer by using a 34 orthogonal design. The results showed that the average yield, output value and net income of all treatment plots were increased by 29%, 220% and 262%, respectively, over that of nought-treatment plot as a control. The shooting start date was moved up 20 days than the control and the best one was 55 days ahead of the control. A vast amount of fresh shoots may be sold at a high price on the markets of spring festival and lantern festival. In such cases the economic benefit was largely increased. For this purpose the best way of management selected was that from the end of November to the beginning of December. Urea was applied to the land at a rate of 75g/m, after being fully watered, bamboo forest land was covered with bamboo leaves in 30 cm thickness immediately.